Heartwood Volumes and Katha Yields by Indigenous Method from Dry Type Khair of Central India - Kulkarni, D. H. (Indian Forester, 1956)
Field experiment carried out in the khair forests of Sagar division (M.P.) on the heartwood contents and the katha yields by indigenous method has been described. The results obtained have been tabulated. The scope of the applicability of the data has been indicated.